INNOVATIVE METHODOLOGY FOR CREATING AN ENVIRONMENT OF TOLERANCE TOWARDS STUDENTS WITH DISABILITIES IN GENERAL SECONDARY SCHOOLS (Universal International Scientific Journal, 2026)
This article describes an innovative methodology for creating an environment of tolerance for students with disabilities in general secondary schools. The study analyzes the importance of pedagogical approaches in the process of inclusive education, issues of improving socio-psychological relations between teachers and students. It also substantiates the effectiveness of modern pedagogical technologies, interactive methods and educational work in ensuring the full integration of students with disabilities into the educational process. The article puts forward methodological recommendations that serve to develop an environment of tolerance
Keywords: Inclusive education; tolerance; environment of tolerance